Why is asset-light strategy necessary? An empirical analysis through the lens of cost stickiness. (October 2019) - Zhang, Jidong; Yin, Meiqun; Han, Jing; Aroskar, Rajarshi
Abstract: The widespread trend among firms in the tourism and hospitality industry to adopt an asset-light strategy has enabled the U.S. tourism industry to grow rapidly by shaving off fixed assets. Our paper explores why an asset-light strategy is necessary from the perspective of cost management. Because cost is very "sticky, " meaning it does not change proportionally with changes in revenue, and change in cost is usually lagged, higher cost stickiness leads to lower financial performance. We found that cost stickiness does exist in the tourism and hospitality industry, and an excess of assets is its main determinant. Moreover, we found that management adjusts the amount of assets to reduce the effects of cost stickiness, and these adjustments are much more significant in revenue-declining years. Contributions, limitations, and practical implications are also discussed. Highlights: Cost stickiness exists in the tourism and hospitality industry. Higher cost stickiness leads to lower financial performance. Amount of asset significantly contributes to cost stickiness. Managerial intervention on cost stickiness lags behind the revenue declines. Cost management is the internal driver for the adoption of asset light strategy.